"DO I STAY OR DO I GO?"—JOB CHANGE AND LABOR MARKET EXIT INTENTIONS OF EMPLOYEES PROVIDING INFORMAL CARE TO OLDER ADULTS. (7th December 2012) - Schneider, Ulrike; Trukeschitz, Birgit; Mühlmann, Richard; Ponocny, Ivo
ABSTRACT: This article examines whether providing informal eldercare to an older dependent person predicts employees' intentions to change jobs or exit the labor market and, if so, which particular aspects of both caregiving (e.g. time demands, physical/cognitive care burden) and their current work environment shape these intentions. We used data from a sample of 471 caring and 431 noncaring employees in Austria and split the analyses by gender. We found different aspects of informal caregiving to be associated with the intention to change jobs and with the anticipated labor market withdrawal of male and female workers. A time‐based conflict between informal eldercare and paid work was significantly and positively related to the intended job change of female workers but not of their male counterparts. Flexible work arrangements were found to facilitate the attachment of female workers to their jobs and the labor market. Intentions to exit the labor market of male workers appeared to be triggered by a physical care burden rather than time demands. Copyright © 2012 John Wiley & Sons, Ltd. HIGHLIGHTS We studied the effects of providing informal eldercare on the turnover intention of men and women in a group of workers who were also the main carers providing support to a dependent older person with substantial care needs. The intention of male and female workers to change jobs and exit the labor market is shaped by the different characteristics of informal caregiving. Time‐based conflicts between informal care and paid work are associated with a higher relative risk of anticipating job changes for female workers. Flextime facilitates the job and labor market attachment of female workers with eldercare responsibilities. The intensity of personal care provided to an older relative is significantly positively related to male workers' relative risk of anticipated labor market exit. Care to an older person in need of supervision makes the labor market exit of female workers less likely, lending thus support to the idea of the respite effect of work.